Fluorescence of Deep Infiltrating Endometriosis During Laparoscopic Surgery: A Preliminary Report on 6 Cases. (October 2018) - De Neef, Auriane; Cadière, Guy-Bernard; Bourgeois, Pierre; Barbieux, Romain; Dapri, Giovanni; Fastrez, Maxime
Background . The standard treatment of rectovaginal deep infiltrating endometriosis nodules (RVDIEN) consists in their surgical removal. RVDIEN are anatomically neovascularized. Indocyanine green (ICG) reveals vascularized structures when becoming fluorescent after exposure to near-infrared (NIR) light. This study aims to evaluate if fluorescence-guided surgery can improve the laparoscopic resection of RVDIEN, thus avoiding a rectal perforation. Materials and Methods . Patients with a symptomatic RVDIEN, scheduled for a laparoscopic rectal shaving, were enrolled in the study. Technically, the RVDIEN was targeted and removed with the help of the NIR imager device Image 1 Spies (Karl Storz GmBH & Co KG, Tuttlingen, Germany) or Visera Elite II (Olympus Europe SE & Co KG, Hamburg, Germany), after an intraoperative, intravenous injection of ICG (0.25 mg/kg). Results . Six patients underwent a fluorescence-guided laparoscopic shaving procedure for the treatment of a nonobstructive RVDIEN. Fluorescence of the RVDIEN was observed in all the patients. In one patient, once the main lesion was removed, the posterior vaginal fornix still appeared fluorescent and was removed. No intraoperative rectal perforation occurred. The postoperative hospital stay was 2 days. No postoperative rectovaginal fistula occurred within a median follow-up of 16 months (range = 2-23 months). Conclusion . In this preliminary study, fluorescence-guided laparoscopy appeared to help in separating the RVDIEN from the healthy rectal tissue, without rectal perforation. Moreover, this technique was helpful in deciding if the resection needed to be enlarged to the posterior vaginal fornix.